개정 「시체 해부 및 보존 등에 관한 법률」의 함의와 주요 쟁점 연구 - 차승현(Seunghyun Cha); 박인경(Inkyoung Park); 백수진(Sujin Baik) (생명, 윤리와 정책, 2021)
2021년 4월 8일, 개정된 시체 해부 및 보존 등에 관한 법률이 시행되었다. 개정에 따른 가장 큰 변화는 기증받은 시체 및 시체의 일부를 이용할 수 있는 연구의 범위가 ‘의학의 교육 및 연구’ 에서 ‘의학ㆍ의생명과학의 연구’로 확대되었다는 점이다. 또한, 의과대학 및 종합병원 중에서 법에서 정한 요건을 갖추고 허가를 받은 경우 연구목적으로 시체의 일부를 수집, 보존, 제공할 수있는 제도가 마련된 것이다. 개정된 시체해부법은 시체의 일부를 이용하여 연구하기 전 기관위원회 심의를 받도록 하고 있다. 그런데 시체의 일부를 이용하는 연구는 연구대상자등인 기증자의 생존 사실 외에는 사실상 연구내용이 생명윤리법에 따른 인체유래물연구와 동일할 수 있다. 따라서 기관위원회가 생명윤리법 제10조제3항제1호에 따라 인체유래물 연구를 심의할 때, 연구대상자등의 안전에 관한 사항 이외에 심의 내용이나 기준 등은 달라질 수 없다. 또한, 시체 일부에 대한 연구 시 유족의 동의를 받도록 하고 있는데, 유사례를 다루는 생명윤리법은 인체유래물기증자로부터 자율성에 기반한 자발적 동의를 강조하고 이를 존중하도록 하고 있다. 시체해부법에 따른 동의 역시 본인이 생전에 밝힌 기증 의사를 중심으로 이루어지는 것이 타당하나 유족의 동의에 의존하고 있는 점은 아쉬운 부분이다. 따라서 향후 원칙적으로 기증자 본인의 자기결정권이 우선함을 분명히 하고 이것이 불가한 경우 예외적으로 유족의 동의를 인정하는 방향이 검토될 수 있을 것이다. 더불어 이번 시체해부법 개정에서 본 법에 따라 허가받은 연구를 위한 시체의 일부 제공기관이 시체 해부 및 시체의 일부에 대한 수집, 보존, 제공 등 업무를 안전하고 윤리적으로 수행할 수 있게 그 허가 요건을 마련한 것도 중요한 의의라 할 것이다. 시체 및 시체의 일부 활용이 확대됨에 따라, 기증에 동의한 자와 유족에 대한 예우 방안도 그 숭고한 뜻을 해치지 않는 범위 내에서 적절하게 마련될 필요가 있다. 따라서 직접 비용이 지급되는 방식이 아니라 고인과 유족에 뜻에 맞고 예에 따른 장례 절차를 지원할 수 있도록 적절한 제도 마련이 필요할 것이다. On April 8, 2021, the revised Act on Dissection and Preservation of Corpses was implemented. The biggest change is a shift in the research scope, from “Education and Research in Medicine” to “Research in Medicine and Biomedicine.” It set up a system to allow corpse parts to be collected, preserved, and provided for the purpose of research in case the institutions, including not only medical schools but also general hospitals that obtain the permission after meeting legal requirements. Indeed, the research using part of a corpse can be same as the research on human biological material based on the Bioethics and Safety Act, except that the donor is not alive. Therefore, the review of the institutional bioethics committee in accordance with Article 10, Paragraph 3, Item 1 of the Bioethics Act cannot be different to that of human biological material research except the matters concerning the safety of research subjects. In addition, the voluntary consent of donors is emphasized and respected. It is inconvenient that the consent according to the Corpse Dissections Act still relies on the consent of the bereaved family rather than the intent of the donor during her/his lifetime. It can be considered that the donor’s right to self-determination take precedence in principle, and if this is not possible, the consent of the bereaved family should be honored. Furthermore, it is also a significant to implement the permit system according to the revised Act on the Dissection of Corpses to establish institutional requirements for ethical and safe management of the dissection of dead body and the handling of body parts’ collection, preservation, and provision. Additionally, this requires a respectful follow-up plan and support of the donor and families who consent to the use of corpses and body parts without harming the meaning of their supreme sacrifices. Therefore, it is necessary to create an appropriate system to support the honorable funeral services, consistent with the desires of the deceased and their families. KCI Citation Count: 1